Pemanfaatan Dana Desa untuk Pembangunan Infrastruktur Publik (Studi Kasus di Desa Sumberdadi, Kecamatan Sumbergempol, Kabupaten Tulungagung) - Cholifah, Nurul; Diniati, Bintis Ti’anatud; Exsaputra, Muhammad Zakky; Wati, Ira Herlina; Jannah, Kartika Indah Kurniatul (Jurnal EMT KITA, 2026)
This study analyzes the utilization of village funds for infrastructure in Sumberdadi during 2023–2025. The aim is to assess transparency, accountability, and reporting practices. A qualitative approach was used, with data collected from interviews, documents, and field observations. Findings show that all infrastructure projects were completed and reported, but the proportion of funds allocated for infrastructure decreased each year. The study concludes that the utilization of village funds followed governance principles, although budget priorities shifted over time.